Jobs at play and jobs that pay. - Heubusch, Kevin (American Demographics, 1998)
The number of U.S. jobs is projected to rise by 12.7 percent between 1998 and 2010, to nearly 172 million, according to Woods & Poole Economics Inc., Washington, D.C. These new jobs are most likely to be in the Southern and Western counties. According to George Silvestri, a labor economist at the Bureau of Labor Statistics (BLS), most job growth through at least 2006 will take place in the services industry. However, of the nine broad industries tracked by the BLS, services comes second-to-last in average wages. The best-paying new jobs in 2010 are most likely to be in metropolitan areas where economies are more diverse. Details of the job projections are provided, and maps illustrate the geographical spread of projected U.S. employment from 1998 to 2010 and projected manufacturing, construction, and services employment from 1998 to 2010.